Determinant Analysis of Open Unemployment Rate in West Java Province (Universitas Negeri Semarang, 2022)
Unemployment is a condition where individuals belonging to the workforce want to get a job but have not yet found a job. One of the unemployment problems that needs to be solved immediately is Tingkat Pengangguran Terbuka. Tingkat Pengangguran Terbuka is the percentage of the number of unemployed to the total labor force. This study aims to determine the determinants of TPT in West Java Province. The data source used comes from BPS for the 2018-2021 period where the determinants of TPT include PDRB, IPM, population, TPAK, and LPP. Data analysis used panel data regression with the Fixed Effect Model (FEM) approach. The results showed that simultaneously PDRB, IPM, population, TPAK, and LPM had an effect on TPT. Partially, PDRB has a significant negative effect on TPT, IPM has a non-significant negative effect on TPT, population has a significant positive effect on TPT, TPAK has a non-significant negative effect on TPT, and LPP has a non-significant positive effect on TPT. The coefficient of determination (R2) shows the number 0.877 which means that the total variation in TPT in West Java Province in 2018-2021 can be explained by PDRB, IPM, population, TPAK, and LPM of 87.7%..